Improvement of Cyclodextrin Glucanotranferase (CGTase) Secretion by Recombinant Escherichia Coli Immobilized on Hollow Fiber Membrane Using Full Factorial Design - Rohaida, Che Man; Ahmad Fauzi, Ismail; Nazlee Faisal, Ghazali; Rosli, Md. Illias (2014)
Immobilization of cell for enzyme production provides many advantages such as repeated use of cells, capability to separate the cell from the fermentation medium and freedom from toxicity problems. In this study, hollow fiber membrane was used to immobilize Escherichia coli with the intention to improve secretion of enzymes and increase cell viability. Full factorial design was applied to identify the critical and significant parameters on immobilized cell towards CGTase secretion and cell viability. The parameters involved in this screening study were temperature, inducer concentration, agitation rate, post induction time and pH. The results show that only temperature, inducer concentration and pH have significant effect on immobilized cell for CGTase secretion and cell viability. Under the significant conditions (25°C, 0.005 mM IPTG and pH 9), the secretion of CGTase was 128- fold increased with 90% reduction of cell lysis compared to one factor at a time method.